2008
DOI: 10.1159/000121906
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Perforations from Abdominal Trauma

Abstract: Background: Gastric rupture due to abdominal trauma is rare (0.02–1.7%); it is usually caused by traffic accidents. Delayed diagnosis, abdominal contamination and associated lesions cause morbidity and mortality. Patients and Methods: Retrospective review of 2,083 patients with abdominal traumatism treated at our center over 20 years. We reviewed recent ingestion of a meal, etiology, time to surgery, site, Stomach Injury Scale, abdominal contamination, treatment, associated injuries, complications and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
2
9
0
2
Order By: Relevance
“…However, 78% of all deaths between the ages of 15 and 24 years are due to trauma [27]. In our study, most patients with penetrating gastric trauma were young adult males, concurring with the findings of previous reports [14,28]. Similarly, age and sex were not associated with the outcome of penetrating gastric injury in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, 78% of all deaths between the ages of 15 and 24 years are due to trauma [27]. In our study, most patients with penetrating gastric trauma were young adult males, concurring with the findings of previous reports [14,28]. Similarly, age and sex were not associated with the outcome of penetrating gastric injury in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Isolated gastric injuries due to abdominal trauma are rare; gastric injuries are usually accompanied by abdominal or extra-abdominal organ injuries [7,10,13]. As in our study, the most frequently reported accompanying injured abdominal organs are the small intestine and colon, and the most frequently injured extra-abdominal organs are the lungs and pelvis [14].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Tertiary surveys may detect significant injuries missed during primary and secondary surveys. 7 Gastric injuries are usually associated with a high injury severity score.…”
Section: Discussionmentioning
confidence: 99%
“…1,6−8 The most commonly affected part of the stomach is the anterior stomach wall (40% of total gastric injuries), followed by the greater (23%) or lesser (15%) curvature of the stomach and the posterior stomach wall (15%). 7 Most gastric injuries are superficial haematomas and serosal tears, whereas full thickness perforations occur less commonly (0.3%). 1 A proposed classification for traumatic gastric Patients with gastric injuries secondary to BAT usually have a nonspecific presentation, possibly due to shock; as such, abdominal tenderness or rigidity and fevers are less likely to be clinically evident.…”
Section: Discussionmentioning
confidence: 99%